Validation of the Drinking Motives Questionnaire - Revised in six European countries. (November 2016) - Fernandes-Jesus, Maria; Beccaria, Franca; Demant, Jakob; Fleig, Lena; Menezes, Isabel; Scholz, Urte; de Visser, Richard; Cooke, Richard
Highlights: This paper assesses the validity of the DMQ-R (Cooper, 1994) among university students in six different European countries. Results provide support for similar DMQ-R factor structures across countries. Drinking motives have similar meanings among European university students.